Pandemic Adaptation: Online Study Could be Interesting and Enjoyable with Games : Adaptasi Pandemi: Belajar Online Bisa Jadi Menarik dan Menyenangkan dengan Permainan - Nugraheni, Elizabeth; Ritunga, Imelda; Harsa, Cempaka (Universitas Muhammadiyah Sidoarjo, 2025)
Adapting offline to online learning during the pandemic requires interactive design so that students can stay involved and achieve learning goals. Interactive and fun learning will motivate student learning. We design PBL learning using interactive and collaborative games in online meetings. The aim of this research is to see students' learning motivation in PBL using online games. This research is a cross-sectional descriptive class participation study. PBL games in the form of scenarios are presented in the form of online images with hidden keywords and students work together in groups to find solutions. First year students are asked to fill out the Intrinsic Motivation Inventory (IMI) questionnaire at the end of the PBL games activity. Students rated PBL games as fun (71%), beneficial (69%), and provided choices (33%). The increase in students' intrinsic motivation can be seen in the high percentage of fun and beneficial components. The PBL learning method using games can increase students' intrinsic motivation. Learning methods using games can be developed and used continuously so that learning is interesting and fun.